Investigation Of In Vitro Permeation Of Mitragynine Through The Skin - Sim, Yee Shan (2023)
Mitragynine is an alkaloid isolated from the leaves of the Mitragyna speciosa plant and has been traditionally consumed in the form of tea concoctions. Recent studies theorised mitragynine to be a potential candidate for pain relief and the treatment of opiate withdrawal symptoms as a replacement therapy. Due to mitragynine’s poor oral bioavailability, the delivery of mitragynine through the skin is proposed in this study. However, the investigation of in vitro permeation of mitragynine through the skin is deemed to be lacking. This study aims to investigate the potential of delivering mitragynine using various solvents through the skin, with emphasis to improve, optimise and validate methods to evaluate the permeation of mitragynine across the skin. Mitragynine was characterised using differential scanning calorimetry, attenuated total reflectance-Fourier transform infrared spectroscopy and x-ray diffraction. Mitragynine utilised in this experiment was found to be likely amorphous. A high-performance liquid chromatography analytical method with an ultraviolet detector was optimised and validated according to the International Council of Harmonisation guidelines. The analytical method was found to be precise, accurate and robust which successfully eluted a sharp mitragynine peak at ~4 min with an acceptable tailing factor of 1.32. The experimental method for the in vitro permeation studies using Franz diffusion cells was optimised and ascorbic acid was used as an antioxidant in the receptor compartment. In vitro permeation studies were conducted using dissolved mitragynine in simple solvent systems of various solvents. The solvents employed in this study were found to have the ability to solubilise and assist the permeation of mitragynine through the skin.